Analisis Kepuasan Pengguna Aplikasi Renshuu dalam Pembelajaran Bahasa Jepang Menggunakan Metode UEQ - Rasendriya, Achmad Syahmi; Halimi, Keysha Maulina; Salsabila, Alya Putri; Aji, Wahyu Mustika; Lestari, Humannisa Rubina (Jurnal Bahasa Jepang Taiyou, 2025)
This study examines user satisfaction with the Renshuu application for Japanese language learning using the User Experience Questionnaire (UEQ) method. The research aims to evaluate user experience aspects, including support, ease of use, efficiency, clarity, excitement, interest, innovation, and modernity. Data were collected by 25 active Renshuu users. Quantitative analysis revealed average scores across all UEQ dimensions in the "Excellent" category (1.75–2.00 on a -3 to +3 scale), with the highest scores in clarity (mean = 2.00) and interest (mean = 2.00), and the lowest in modernity (mean = 1.76). Users rated Renshuu as effective for self-paced learning due to its interactive interface, gamified features, and A scheduling system. Qualitative findings highlighted adaptive quizzes, engaging visual designs, and Discord community support as key satisfaction drivers. Additionally, users noted Renshuu’s superiority over similar platforms like Duolingo in content depth and flexibility. The study concludes that Renshuu not only fulfills functional (pragmatic) needs but also delivers an enjoyable (hedonic) learning experience, positioning it as a recommended tool for further development, particularly in advanced content and adaptive technology integration.